IMPLEMENTASI PENDEKATAN PARTISIPATIF DALAM SOSIALISASI PENCEGAHAN LEPTOSPIROSIS: PENGALAMAN KELOMPOK 3 KKN NUSANTARA 2025 DI PADUKUHAN SAYANGAN, KULON PROGO, D.I.YOGYAKARTA - Fahmi, Zul; Ngaliyah Dwi Lestari; Nufair Ahmad Syihan; Farah Nishful Laily; Ishaq Ishaq; Talita Alba Salsabila (CV. Denasya Smart Publisher, 2025)
This article discusses a socialization activity themed “Be Aware of Leptospirosis: Recognize, Prevent, and Address Before It's Too Late,” conducted by Group 3 of the Nusantara 2025 Community Service Program on August 10, 2025, at the Pendopo Padukuhan Sayangan, Banjararum Village, Kalibawang Sub-district, Kulon Progo District. The activity was attended by local PKK cadres and facilitated by 13 students from various PTKIN and PTKIS institutions, with dr. Augrey Prawita as the speaker. The objective of the activity was to provide basic understanding regarding the etiology, transmission routes, clinical signs, simple preventive measures, and initial actions to be taken if infection is suspected. The methods used were descriptive and educational, including presentations by medical personnel, simple practical demonstrations, and interactive question-and-answer sessions. Activity documentation included attendance lists, photos, copies of materials, and question-and-answer notes. No quantitative measurements were taken, so the analysis was narrative-based, relying on observations and facilitator notes. Results showed active participant engagement during the question-and-answer session; questions raised included distinctions between fever symptoms, household prevention measures, the role of animal reservoirs, and referral procedures. Facilitator observations indicated increased awareness and participants' intent to share information with family members, though changes in knowledge or behavior were not measured numerically. Documentation of activities was recorded in full as evidence of implementation. The conclusion stated that the socialization was successfully implemented according to plan and increased initial awareness among participants. The main limitations were that it was a one-time implementation and there was no quantitative evaluation. Recommended follow-up actions included cadre training, provision of visual materials, coordination with community health centers, and coordinated environmental activities to strengthen leptospirosis prevention.